Peran Notaris dan PPAT dalam Proses Peralihan Hak atas Tanah - Rifky Astriansyah; Habieb Ahmad Al Musyaddady (Sharia Faculty of Universitas Islam Negeri Maulana Malik Ibrahim Malang, Indonesia, 2026)
The transfer of land rights is a cornerstone of Indonesian land law, designed to guarantee legal certainty and protect the rights of the community. This process, whether facilitated through sales, grants, or inheritance, relies heavily on the expertise of notaries and Land Deed Officials (PPAT), who are tasked with ensuring the legitimacy of these transactions. Notaries are responsible for drafting authentic deeds and offering legal counsel, while PPATs specialize in creating land rights transfer deeds and overseeing administrative compliance, including the payment of the Land and Building Acquisition Duty (BPHTB). This study employs a qualitative approach with descriptive analysis, drawing on a comprehensive review of existing literature and regulations. By analyzing these sources, the research highlights the pivotal role notaries and PPATs play in fostering a land system that is transparent, accountable, and less prone to disputes. The findings underscore that the responsibilities of notaries and PPATs extend beyond deed creation to include land status verification, abuse prevention, and adapting to digital administration systems. Professionalism, integrity, and technological adaptability are essential in ensuring that land rights transfers are legally sound, efficient, and offer certainty to all stakeholders.